Dimsum Makteng Msme Development Strategy In Islamic Economic Studies - Apriliani Alicia Putri (Universitas Trunodjoyo Madura, 2025)
This research aims to analyze the development strategy of Dimsum Makteng SME from an Islamic economic perspective. Using a qualitative approach and case study method, this research applies MVPO (Mission, Vision, Programs, Outcomes) analysis and SOAR analysis as analytical frameworks. The results show that Dimsum Makteng has implemented four main strategies: product diversification, marketing digitalization, human resource optimization, and operational efficiency. The main challenge lies in the use of capital from conventional banks that potentially contain elements of riba (usury). Strategic recommendations include capital restructuring using Islamic financing schemes, strengthening business practices based on Islamic values, and developing Islamic business networks. This research contributes to the integration of Islamic economic principles in SME development and provides practical implications for micro-business actors in implementing sharia business strategies.Keywords: SMEs, Development Strategies, Islamic Economics, Dimsum Makteng